At “half mask” or “nose commando:” A note demonstrating nasal breaths can spread microorganisms when improperly wearing a mask during COVID-19 - Robert J. Wolff (Microbiologia Medica, 2020)
Many individuals are wearing face masks improperly at ‘half mask’ and potentially breathing out microbes that can contaminate the air as well as anything below the nose. This note provides the first report that bacteria and fungi breathed out during nasal air exhalation are able to be cultured after landing on blood agar plates. The CFU’s are higher after both 10 breaths and extremely significant for 20 breaths compared to the control plates exposed to the air. Implications of this finding are that going ‘nose commando’ may be able to continue the spread of respiratory diseases such as COVID-19. Minute bioaerosols carrying bacteria may be designated as microsnot.